INTERETHNIC RELATIONS IN THE NORTHERN REGION OF COSTA RICA 1900 – 1910 - Madrigal Córdoba, Javier (2024)
The following article presents an approach to interethnic relations in the Northern Region of Costa Rica during the first decade of the 19th century. Its purpose is to describe the process of formation of new towns due to the migration of peasants from both Costa Rica and Nicaragua and the impact on the Malecu indigenous people. Furthermore, the role of the state as a key actor in the new interethnic relations in the region is analyzed. Through documentary analysis of sources from various archives, media and official statistics, the process of formation of the region is analyzed and the new transformations implied a change in the landscape and cultural relations.